(untitled) (Global Journal of Science Frontier Research, 2015)
Polymorphic DNA markers are widely used to study genomic diversity, as most of them are selectively neutral, more ubiquitous than polymorphic protein and enzyme markers. Therefore, it is of great interest to study the genomic diversity and their relationships among the four south Indian tribal populations DNA samples from 190 unrelated individuals belonging to four Dravidian tribal populations viz. Malaikuravan, Malasar, Palliyan and Kattunaikkan were analysed by nine human specific insertion / deletion polymorphic loci and nine restriction site polymorphic loci to ascertain their genomic diversity and affinities with other Indian tribal populations. The results indicate that most of the studied loci are highly polymorphic in terms of allele frequencies (average allele frequency=0.51) and average heterozygosity (H T = 0.49) in all the study populations. The genomic diversity (G ST ) of the four tribal populations was comparatively low (0.032).